Congenital syphilis in Switzerland: a retrospective cohort study, 2010 to 2019 - Gioia Scherler; Maren Tomaske; Vincenzo Cannizzaro; Anna Steppacher; Franziska Zucol; Martin Theiler; Laurence Toutous Trellu; Anton Labutin; Philipp P. Bosshard; Christoph Berger; Patrick M. Meyer Sauteur (Swiss Medical Weekly, 2023)
AIMS OF THE STUDY: We previously reported a re-emergence of syphilis from 2006 to 2009 with detection of congenital syphilis in Switzerland. This study aimed to reassess the incidence of children exposed to maternal syphilis during pregnancy and congenital syphilis in a following 10-year period in the canton of Zurich, the most populous canton in Switzerland with the highest incidences of syphilis.